1975
DOI: 10.1007/bf00422322
|View full text |Cite
|
Sign up to set email alerts
|

Human C-peptide in normal and diabetic subjects

Abstract: Concentrations of human C-peptide, IRI (immunoreactive insulin) and glucose were determined during oral glucose tolerance test (1.75 g glucose/kg ideal body weight) in 14 normal persons (N), 9 maturity-onset diabetics (DI) and 10 insulin-requiring diabetics (DII) never treated with insulin and in 3 formerly insulin treated diabetics. The mean fasting levels of C-peptide and IRI in the first three groups were: N: 0.37 +/- 0.02 nM and 0.048 +/- 0.009 nM, DI: 0.86 +/- 0.17 nM and 0.11 +/- 0.029 nM, DH: 0.37 +/- 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
43
0

Year Published

1977
1977
2014
2014

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 105 publications
(47 citation statements)
references
References 12 publications
4
43
0
Order By: Relevance
“…retain modest beta-cell activity, allowing for the production of low levels of C-peptide (9,10,20). In a study analyzing patient tertiles based on C-peptide levels, the incidence of retinopathy, nephropathy, and neuropathy decreased from the first (Cpeptide Յ 0.47 nM) to the third tertile (C-peptide Ն 0.80 nM) (7).…”
Section: Discussionmentioning
confidence: 99%
“…retain modest beta-cell activity, allowing for the production of low levels of C-peptide (9,10,20). In a study analyzing patient tertiles based on C-peptide levels, the incidence of retinopathy, nephropathy, and neuropathy decreased from the first (Cpeptide Յ 0.47 nM) to the third tertile (C-peptide Ն 0.80 nM) (7).…”
Section: Discussionmentioning
confidence: 99%
“…Fasting serum concentrations may be within the normal nondiabetic range (5) at the time of diagnosis of diabetes (4,12), but decline subsequently (12,13). ~ntibodies directed against pancreatic islet cells (ICA) have been detected in the serum of more than one-half of newly diagnosed insulin-dependent diabetics (8, 1 l).…”
Section: Speculationmentioning
confidence: 99%
“…Recently the immunoassay system of human C-peptide of insulin has been developed by Melani et al (1970a), and Kaneko et al (1974), and many clinical results on the plasma or urine C-peptide immunoreactivity (CPR) have been reported in various diseases, especially in patients with [insulinoma or in insulin-treated diabetic subjects (Block et al, 1972(Block et al, , 1973Horwitz et al, 1975;Heding and Rasmussen, 1975;Kuzuya et al, 1977;Jaspan et al, 1977). The PLC contents of pancreas from diabetic and nondiabetic subjects were already studied (Rastogi et al, 1973;Hayashi et al, 1977), but the amount of C-peptide in human pancreas has not been reported.…”
Section: Synopsismentioning
confidence: 99%